Protein, dietary fiber, minerals, antioxidant pigments and phytochemicals, and antioxidant activity in selected red morph Amaranthus leafy vegetable - Sarker, Umakanta (PLoS One, 2019)
Amaranth has two morphological types (morphs), one is red and another is green morph. Red morph amaranth is a marvelous source of nutrients, antioxidant pigments, minerals, and phytochemicals compared to green morph amaranth. For this purpose, we selected 25 red morph genotypes to evaluate in terms of proximate, minerals, antioxidant pigments and phytochemicals and antioxidant activity in RCBD design in three replicates. The leaves of red morph amaranth are an excellent source of dietary fiber, carbohydrates, moisture, and protein. We found remarkable potassium, calcium, magnesium (24.96, 10.13, 30.01 mg g(-1)), iron, manganese, copper, zinc (1089.19, 243.59, 25.77, 986.61 μg g(-1)), chlorophyll a, chlorophyll b (31.79, 16.05 mg 100 g(-1)), β-cyanins, total flavonoids (102.10 RE μg g(-1) DW), β-xanthins, betalains (33.30, 33.09, 66.40 μg 100 g(-1)), carotenoids, total phenolics (172.23 GAE μg g(-1) DW), β-carotene (1225.94, 1043.18 μg g(-1)), vitamin C (955.19 μg g(-1)), and antioxidant activity (DPPH and ABTS(+)) (19.97 and 39.09 TEAC μg g(-1) DW) in the red morph amaranth leaves. We can select the genotype RA5, RA8, RA18, RA22, and RA25 as antioxidant-enriched red morph amaranth. It revealed that amaranth β-cyanins, phenolics, betalains, flavonoids, β-xanthins, carotenoids, vitamin C, and β-carotene had strong antioxidant activity. These phytochemicals contributed significantly in the antioxidant potentials of red morphs amaranth. Red morph amaranth could be a potential source of nutrients, antioxidant pigments, minerals, and phytochemicals as these compounds scavenged ROS and served as potential antioxidants in our daily diet to attaining nutritional and antioxidant sufficiency.